Coagulômetro para usuários de Varfarina - Pedrotti, Tainá (2024)
Blood clotting is an essential process to prevent excessive bleeding in case of injury to blood vessels. The use of Warfarin, a vitamin K inhibitor, is crucial in the treatment of venous thromboembolism and requires careful monitoring of coagulation levels to balance the risks of thrombosis and hemorrhage. Coagulometers play a vital role in this monitoring, ensuring correct dosage and minimizing complications. Precise control is essential, as both underdosing and overdosing Warfarin can result in serious adverse events. There is a great need for rapid, low-cost, and easily accessible tests, especially for people in areas with limited access to laboratories. This work presents the creation of a prototype coagulometer for Warfarin users, capable of measuring blood clotting time. The validated method involves capturing images of blood during the clotting process using an ESP32-CAM microcontroller with an OV2640 camera and sending these images to a server via HTTP. The server processes the images and returns the clotting time. This approach allows for remote analysis, making it useful in regions with limited access to laboratory equipment.